2018
DOI: 10.4317/jced.54963
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspartame and pH changes on the erosive potential of cola drinks in bovine enamel: An in vitro study

Abstract: BackgroundThe aim of this study was to clarify the mechanism behind the different erosive potential of regular and light cola drinks: pH difference and/or aspartame presence.Material and MethodsSixty bovine enamel blocks were randomly divided into 5 groups: RC - regular cola, RCpH - addition of base to increase regular cola pH, RCAS - addition of aspartame to regular cola, LC - light cola, and LCpH - addition of acid to decrease light cola pH. Two-thirds of the blocks surface was coated with nail varnish for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Phenylalanine contains carboxylic and amino groups that can capture hydrogen ions in the erosive acids and can reduce the acidity of the acids [ 119 ]. Hence, it can reduce the demineralisation of the enamel surface [ 119 , 120 ].…”
Section: Anti-erosive Agents In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Phenylalanine contains carboxylic and amino groups that can capture hydrogen ions in the erosive acids and can reduce the acidity of the acids [ 119 ]. Hence, it can reduce the demineralisation of the enamel surface [ 119 , 120 ].…”
Section: Anti-erosive Agents In the Literaturementioning
confidence: 99%
“…A previous study showed that the anti-erosive effect of aspartame is limited [ 120 ]. All in situ and in vitro studies that investigated the anti-erosive property of aspartame revealed aspartame had no significant protective effect on the bovine enamel compared to no treatment [ 119 , 120 ].…”
Section: Anti-erosive Agents In the Literaturementioning
confidence: 99%
“…The majority of the undiluted samples n= 38/45 (84%) had a pH below 5.5, indicating erosive potential was not predicted by the flavour. The 4 orangesamples ranged from 3.56-6.23 and both cola-samples were higher than anticipated (pH=5.04-5.63), given the pH of cola drink is less than pH 3 15 . In addition, products that were predicted to be non-acidic such as vanilla showed considerable variation ranging from pH 4.69-5.63.…”
Section: Resultsmentioning
confidence: 70%
“…The tooth fragments were immersed, depending on the group, individually in 25 ml of apple vinegar with a pH of 2.44 (Castelo™, SP, Brazil) for two minutes, and in 25 ml of lime juice with a pH of 2.4 (Castelo™, SP, Brazil) for two minutes, under mild agitation, once a day, for three weeks. Later, the fragments were washed with distilled water for one minute, dried, and stored in artificial saliva for the time remaining (Rios et al, 2018).…”
Section: Immersion In Acidic Food Beveragementioning
confidence: 99%